Recent dynamics in the Portuguese housing market as compared with the European Union - Matos Fátima Loureiro De (Bulletin of Geography. Socio-Economic Series)
The closing years of the 20th century witnessed profound changes in the European housing market, characterised by an increase in owner-occupied housing; instability of house prices (leading to a serious crisis in some regions, in light of a fall in demand); a change in people’s attitude to the housing market, involving a rise in the importance of location, the quality of materials and spaces, environmental sustainability, and architectural and urban innovation.